Steroid-responsive dual neuronal antibody-positive paraneoplastic encephalitis - Vani, Nemalidinne Krishna; Anand, Rajiv; Rehani, Varun (Indian Journal of Case Reports, 2024)
Here, we report the case of an elderly African male with multifocal neuraxial involvement in the form of progressive parkinsonism and ataxia over a year. On evaluation, dual neuronal antibody positivity was detected. A diagnosis of paraneoplastic encephalitis was made without any detection of primary neoplasm. He was successfully managed with pulse steroid therapy followed by oral steroid and steroid-sparing oral immunosuppressive drug without any need for intravenous immunoglobulin or plasma exchange.